A method for recovering graphite powder from waste lithium batteries

The graphite negative electrode material of waste lithium battery is separated and picked and washed by dissolving binder, flocculation and filtration, and purifying the waste of resources and environmental pollution in the existing technology, and efficient and environmentally friendly graphite recycling and purification are achieved. .

CN116375022BActive Publication Date: 2025-02-07CAMEL GRP RESOURCE CYCLE XIANGYANG CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310362789.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-06
Publication Date
2025-02-07
Estimated Expiration
2043-04-06

AI Technical Summary

Technical Problem

The prior art is difficult to effectively recycle and purify graphite negative electrode materials in waste lithium batteries, resulting in waste of resources and environmental pollution.

Method used

By using the principles of different bonding properties of positive and negative electrodes of the battery, dissolving the binder, post-flocculation and filtration pressing, etc., the graphite negative electrode material of the waste lithium battery is separated, and purified by pickling, water washing and other operations, reaching more than 99.9% purity.

Benefits of technology

It realizes efficient recycling and purification of graphite negative electrode materials, reduces dependence on mineral resources, reduces energy consumption and pollutant emissions in the production process, and responds to the requirements of "carbon neutrality".

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116375022B_ABST
    Figure CN116375022B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for recovering graphite powder from waste lithium batteries. The method for recovering graphite powder comprises the following steps: pre-treating waste lithium batteries to obtain battery cores, immersing the battery cores in water, stirring to separate graphite on the negative electrode copper foil current collector, obtaining a mixed slurry, filtering the positive electrode and performing subsequent treatment; adding a flocculant to the mixed slurry, standing it for suction filtration and separation to obtain a graphite material; acid-washing the graphite material, then washing it with water, and finally drying it to recover graphite powder. The present invention obtains graphite powder with a total metal impurity content of less than 0.1% and a carbon content of more than 99.5%, thereby improving the economic benefits of recycling lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery recycling, and in particular relates to a method for recycling graphite powder from waste lithium batteries. Background Art

[0002] At present, the research on negative electrode materials for lithium-ion batteries is very extensive, and carbon-based and non-carbon-based materials such as silicon-based materials, mesophase carbon microspheres, and graphene negative electrode materials are emerging in an endless stream. However, graphite currently firmly occupies the negative electrode material market due to its early development, mature technology, low price, good conductivity, ordered layered structure, and actual specific capacity density that is close to the theoretical specific capacity.

[0003] At the same time, the rise of the new energy vehicle market has increased the demand for lithium batteries. As time goes by, a large number of power batteries are facing retirement. It is estimated that by 2025, the number of lithium batteries that need to be recycled will reach nearly one million tons, becoming the starting point of the power battery retirement wave. Most graphite negative electrode materials are artificial graphite. In the process of raw material preparation and cost production, a large amount of dust and carbon dioxide will inevitably be generated. By recycling and reusing the negative electrode graphite materials of waste lithium batteries, the reuse of resources is achieved.

[0004] In view of this situation, it is necessary to provide a simple method for recycling the negative electrode graphite material of waste lithium batteries so as to better solve the above problems. Summary of the invention

[0005] In view of the existing deficiencies, the purpose of the present invention is to provide a method for recovering graphite powder from waste lithium batteries. The present invention utilizes the principle that the positive and negative electrodes of the battery have different adhesiveness, separates the graphite negative electrode material of the waste lithium battery by dissolving the binder, flocculating and then filtering, and then purifies it by acid washing, water washing and other operations, recovers the negative electrode material of the waste lithium ion battery and prepares graphite with a purity of more than 99.9%, which has the advantages of simple operation and the like.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A method for recovering graphite powder from waste lithium batteries comprises the following steps:

[0008] S1: water-soluble binder, stirred to obtain mixed slurry

[0009] The waste lithium battery is pre-treated to obtain a battery core, which is immersed in water and stirred to separate the graphite on the negative electrode copper foil current collector to obtain a mixed slurry, and the positive electrode is filtered and then subsequently treated;

[0010] S2: Flocculation and filtration to obtain graphite material

[0011] Since high temperature cracking is not performed, electrolyte and binder exist in the mixed slurry S1, which makes the system of graphite powder and water very stable and difficult to settle naturally and filter. Add flocculant to the mixed slurry in S1, let it stand and then filter and separate it by suction to obtain graphite material;

[0012] S3: pickling, washing, drying

[0013] The graphite material in S2 is acid-washed, then water-washed, and finally dried to recover graphite powder.

[0014] Preferably, in S1, the pretreatment method is: first dismantling the waste lithium battery, and then removing the battery shell or aluminum-plastic film from the undischarged battery cell.

[0015] Preferably, in S1, the stirring time is 15 to 60 minutes.

[0016] Preferably, in S2, the volume ratio of the flocculant to the mixed slurry is 1:5-15.

[0017] Preferably, in S2, the flocculant is an alum solution or a ferrous sulfate solution.

[0018] Preferably, in S2, the concentrations of the alum solution and the ferrous sulfate solution are both 5-8 wt%.

[0019] Preferably, in S2, the standing time is 30 to 60 minutes.

[0020] Preferably, in S3, the pickling is performed using a sulfuric acid solution.

[0021] Preferably, the concentration of the sulfuric acid solution is 2 to 3 mol / L.

[0022] Preferably, the mass ratio of the sulfuric acid solution to the graphite material is 5 to 15:1.

[0023] Preferably, the pickling is performed 1 to 2 times.

[0024] Preferably, the mass ratio of water for washing to graphite material is 5 to 15:1.

[0025] Preferably, the number of water washings is 1 to 2 times.

[0026] Compared with the prior art, the beneficial effects of the present invention include:

[0027] (1) Before the battery is crushed and recycled, it needs to be discharged. The most commonly used discharge method is salt water discharge. The method provided by this application avoids the battery discharge operation, reduces the waste gas and waste water generated by salt water discharge, and reduces the treatment cost.

[0028] (2) The method provided in the present application obtains a complete positive electrode sheet, copper foil current collector and negative electrode graphite material by dissolving the binder, flocculating and then filtering. The negative electrode graphite material is purified by multiple acid washing and water washing, and high-purity graphite is recovered. The recovered graphite can be used as a principle for reproduction. It reduces the mining of various minerals, helps to reduce energy consumption in the graphite production process, reduces pollutant emissions, and responds to the requirements of "carbon neutrality".

[0029] (3) This application compares a variety of different flocculants and screens out flocculants such as ferrous sulfate, which significantly improve separation. In addition, by controlling the amount of addition, the introduction of impurity ions is reduced, and subsequent simple treatment methods such as acid washing and water washing are used to remove impurities, thereby reducing the processing cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The present invention is a flow chart of the method for recovering graphite powder from waste lithium batteries.

[0031] Figure 2 This is a comparison chart of the flocculation effects of PAC, PAM and ferrous sulfate. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] Example 1

[0034] A method for recovering graphite powder from waste lithium batteries, comprising the following steps:

[0035] S1: water-soluble binder, stirred to obtain mixed slurry

[0036] Manually remove the aluminum-plastic film on the outside of the undischarged soft-pack battery cell to obtain the internal integral electrode. In a well-ventilated place, completely immerse the battery cell in deionized water and mechanically stir it for 20 minutes to completely remove the graphite on the copper foil current collector, pick up the positive electrode sheet, separator and copper foil current collector to obtain a mixed slurry.

[0037] S2: Flocculation and filtration to obtain graphite material

[0038] According to the volume ratio of alum solution to mixed slurry of 1:10, add alum solution with a concentration of 5wt% to the mixed slurry while stirring. After the addition is completed, let it stand for 30 minutes, and obvious stratification will be observed. At this time, filter and separate to obtain graphite material.

[0039] S3: pickling, washing, drying

[0040] The graphite material obtained by filtration was acid-washed twice with 2 mol / L sulfuric acid according to a mass ratio of sulfuric acid to graphite material of 10:1, and then washed once with deionized water according to a mass ratio of water to graphite material of 10:1. The graphite after washing was placed in an oven for drying to collect powdered graphite.

[0041] The graphite powder prepared in Example 1 was detected and analyzed using ICP. The analysis results are shown in Table 1.

[0042] Table 1 ICP analysis results of graphite powder obtained in Example 1

[0043]

[0044] From the analysis results in Table 1, it can be concluded that the total amount of conventional metal impurities is less than 0.1%.

[0045] After testing by a carbon-sulfur analyzer, the carbon content is above 99.5%.

[0046] Example 2

[0047] A method for recovering graphite powder from waste lithium batteries, comprising the following steps:

[0048] S1: water-soluble binder, stirred to obtain mixed slurry

[0049] Manually remove the aluminum-plastic film on the outside of the undischarged soft-pack battery cell to obtain the internal integral electrode. In a well-ventilated place, completely immerse the battery cell in deionized water and mechanically stir for 30 minutes to completely remove the graphite on the copper foil current collector, pick up the positive electrode sheet, separator and copper foil current collector to obtain a mixed slurry.

[0050] S2: Flocculation and filtration to obtain graphite material

[0051] According to the volume ratio of ferrous sulfate solution to mixed slurry of 1:10, add ferrous sulfate solution with a concentration of 5wt% to the mixed slurry while stirring. After the addition is completed, let it stand for 30 minutes, and obvious stratification will be observed. At this time, filter and separate to obtain graphite material.

[0052] S3: pickling, washing, drying

[0053] The graphite material obtained by filtration was acid-washed once with 2 mol / L sulfuric acid according to a mass ratio of sulfuric acid to graphite material of 10:1, and then washed twice with deionized water according to a mass ratio of water to graphite material of 10:1. The graphite after washing was placed in an oven for drying to collect powdered graphite.

[0054] The graphite powder prepared in Example 2 was detected and analyzed using ICP. The analysis results are shown in Table 2.

[0055] Table 2 ICP analysis results of graphite powder obtained in Example 2

[0056]

[0057] From the analysis results in Table 2, it can be concluded that the total amount of conventional metal impurities is less than 0.1%.

[0058] After testing by a carbon-sulfur analyzer, the carbon content is above 99.5%.

[0059] Example 3

[0060] A method for recovering graphite powder from waste lithium batteries, comprising the following steps:

[0061] S1: water-soluble binder, stirred to obtain mixed slurry

[0062] The aluminum-plastic film on the outside of the undischarged soft-pack battery cell was manually removed to obtain the internal integral electrode. In a well-ventilated place, the battery cell was completely immersed in deionized water and mechanically stirred for 60 minutes to completely remove the graphite on the copper foil current collector, and the positive electrode sheet, separator and copper foil current collector were picked up to obtain a mixed slurry.

[0063] S2: Flocculation and filtration to obtain graphite material

[0064] According to the volume ratio of ferrous sulfate solution to mixed slurry of 1:15, add ferrous sulfate solution with a concentration of 8wt% to the mixed slurry while stirring. After the addition is completed, let it stand for 30 minutes, and obvious stratification will be observed. At this time, filter and separate to obtain graphite material.

[0065] S3: pickling, washing, drying

[0066] The graphite material obtained after filtration was acid-washed once with 3 mol / L sulfuric acid according to a mass ratio of sulfuric acid to graphite material of 5:1, and then washed once with deionized water according to a mass ratio of water to graphite material of 15:1. The graphite after washing was placed in an oven for drying to collect powdered graphite.

[0067] The graphite powder prepared in Example 3 was detected and analyzed using ICP. The analysis results are shown in Table 3.

[0068] Table 3 ICP analysis results of graphite powder obtained in Example 3

[0069]

[0070] From the analysis results in Table 3, it can be concluded that the total amount of conventional metal impurities is less than 0.1%.

[0071] After testing by a carbon-sulfur analyzer, the carbon content is above 99.5%.

[0072] Referring to the above three embodiments and analysis results, the present invention can recover graphite powder with a total amount of metal impurities less than 0.1% and a carbon content higher than 99.5% through simple operations such as water dissolution, flocculation separation, acid washing, and water washing.

[0073] Flocculant selection experiment:

[0074] The separation effect of PAC, PAM and ferrous sulfate as flocculants on mixed slurry was tested as follows:

[0075] (1) Manually remove the aluminum-plastic film on the outside of the undischarged soft-pack battery cell to obtain the internal integral electrode. In a well-ventilated place, completely immerse the battery cell in deionized water and mechanically stir it for 30 minutes to completely remove the graphite on the copper foil current collector. Then pick up the positive electrode sheet, separator and copper foil current collector to obtain a mixed slurry.

[0076] (2) Add 5 wt% flocculant solution to the mixed slurry at a volume ratio of 1:10 while stirring. After the addition, let it stand for 30 minutes to observe whether there is stratification. The results are as follows: Figure 2 shown.

[0077] from Figure 2 We can see that: comparing the effects of different flocculants, only ferrous sulfate can be observed to have obvious stratification, which can significantly improve the separation efficiency. When using flocculants such as PAC and PAM, no stratification phenomenon can be observed, and there is no obvious improvement in the separation effect.

[0078] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for recovering graphite powder from waste lithium batteries, characterized in that: The steps include: S1: water-soluble binder, stirred to obtain mixed slurry The waste lithium battery is pre-treated to obtain a battery core, which is immersed in water and stirred to separate the graphite on the negative electrode copper foil current collector to obtain a mixed slurry, and the positive electrode is filtered and then subsequently treated; The pretreatment method described in S1 is: first dismantling the waste lithium battery, and then removing the battery shell or aluminum-plastic film from the undischarged battery cell; S2: Flocculation and filtration to obtain graphite material Adding a flocculant to the mixed slurry in S1, letting it stand, and then filtering and separating to obtain a graphite material; S2 The flocculant is ferrous sulfate solution; S3: pickling, washing, drying The graphite material in S2 is acid-washed, then water-washed, and finally dried to recover graphite powder.

2. A method for recovering graphite powder from waste lithium batteries according to claim 1, characterized in that: The volume ratio of the flocculant and the mixed slurry in S2 is 1:5~15.

3. A method for recovering graphite powder from waste lithium batteries according to any one of claims 1 to 2, characterized in that: The concentration of the ferrous sulfate solution in S2 is 5-8wt%.

4. A method for recovering graphite powder from waste lithium batteries according to claim 1, characterized in that: The stirring time in S1 is 15 to 60 minutes; the standing time in S2 is 30 to 60 minutes.

5. A method for recovering graphite powder from waste lithium batteries according to claim 4, characterized in that: S3 The pickling is carried out using a sulfuric acid solution.

6. A method for recovering graphite powder from waste lithium batteries according to claim 5, characterized in that: The concentration of the sulfuric acid solution is 2-3 mol / L.

7. A method for recovering graphite powder from waste lithium batteries according to claim 6, characterized in that: The mass ratio of the sulfuric acid solution to the graphite material is 5-15:1; the mass ratio of the water for washing to the graphite material is 5-15:

1.

8. A method for recovering graphite powder from waste lithium batteries according to claim 7, characterized in that: The acid washing is performed 1 to 2 times; the water washing is performed 1 to 2 times.

Citation Information

Patent Citations

  • Treatment method and application of lithium battery cathode waste liquid

    CN111620423A

  • Regenerated graphite electrode material and preparation method and application thereof

    CN111883772A

  • Separation and recovery method of lithium ion battery negative plate

    CN115632182A